Combing a novel device and negative pressure wound therapy for managing the wound around a colostomy in the open abdomen: A case report. Issue 52 (December 2017) - Sun, Xiaofang; Wu, Shaohan; Xie, Ting; Zhang, Jianping
Abstract: Rationale: An open abdomen complicated with small-bowel fistulae becomes a complex wound for local infection, systemic sepsis and persistent soiling irritation by intestinal content. While controlling the fistulae drainage, protecting surrounding skin, healing the wound maybe a challenge. Patient concerns: In this paper we described a 68-year-old female was admitted to emergency surgery in general surgery department with severe abdomen pain. Resection part of the injured small bowel, drainage of the intra-abdominal abscess, and fashioning of a colostomy were performed. Diagnoses: She failed to improve and ultimately there was tenderness and lot of pus under the skin around the fistulae. The wound started as a 3-cm 2 lesion and progressed to a 6 ×13  (78 cm 2 ) around the stoma. Interventions: In our case we present a novel device for managing colostomy wound combination with negative pressure wound therapy. Outcomes: This tube allows for an effective drainage of small-bowel secretion and a safe build-up of granulation tissue. Also it could be a barrier between the bowel suction point and foam. Lessons: Management of open abdomen wound involves initial dressing changes, antibiotic use and cutaneous closure. When compared with traditional dressing changes, the NPWT offers several advantages including increased granulation tissue formation, reduction in bacterial colonization, decreased of bowel edema and wound size, and enhanced neovascularization.